Dichotomies and Dynamics in Linguistic Pan-Africanism - Ajayi, Samson Abiola (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The language question in Pan-Africanism is as complex as the tortuous historical journey of the black continent is. The age-long efforts at arriving at a single or a very few pan-African languages have been confronted with strong and undeniable realities. This paper examines the complexities, through tree major areas of: the language question itself, the multiple nationalism consciousness, and the centrality of language to not only identity but also development. It concludes that, varied and mountainous as the dichotomies and dynamics of linguistic pan-Africanism may appear, the fact remains that Africa may not get its developmental efforts right until the language issue, vis-Ã -vis education, science and technology, is fixed. Keywords: Language question, dichotomies, dynamics, indigenous languages, development.